Neuronopathic Gaucher disease: Beyond lysosomal dysfunction - Arévalo, Nohela B.; Lamaizon, Cristian M.; Cavieres, Viviana A.; Burgos, Patricia V.; Álvarez, Alejandra R.; Yañez, María J.; Zanlungo, Silvana (Frontiers in Molecular Neuroscience, 2022)
Gaucher Disease (GD) is an inherited disorder caused by recessive mutations in the GBA1 gene that encodes the lysosomal enzyme 𝛃-Glucocerebrosidase (𝛃-GC). 𝛃-GC hydrolyzes glucosylceramide (GluCer) into glucose and ceramide in the lysosome, and the loss of activi-ty leads to GluCer accumulation in different tissues. Enzymatic deficiency triggers inflamma-tion, organomegaly, bone disease, and neurodegeneration in severe cases. Neuronopathic Gaucher disease (nGD) encompasses two different forms of the disease, characterized by chronic or acute damage to the Central Nervous System (CNS). The cellular and molecular studies that uncover the pathological mechanisms of nGD mainly focus on lysosomal dys-function since the lysosome is the key organelle affected in GD. However, new studies show alterations in other organelles that contribute to nGD pathology. For instance, abnormal ac-cumulation of GluCer in lysosomes due to loss in the activity of 𝛃-GC leads to excessive calcium release from the endoplasmic reticulum (ER), activating the ER-associated degrada-tion pathway and the unfolded protein response. Furthermore, recent evidence indicates mi-tophagy impairment in nGD, resulting in the accumulation of dysfunctional mitochondria, a critical factor in disease progression. Additionally, nGD patients present alterations in mito-chondrial morphology, membrane potential, ATP production, and increased reactive oxygen species (ROS) levels. Meanwhile, little is known about dysfunction in other organelles of the secretory pathway, such as the Golgi apparatus and exosomes. This review focuses on collecting evidence about organelle dysfunction beyond lysosomes in nGD. We briefly describe cellular and animal models and signaling pathways relevant to un-covering the pathological mechanisms and new therapeutic targets in GD.